A putative causality of vitamin D in common diseases: A mendelian randomization study - Liu, Hui; Shen, Xudan; Yu, Tunan; Wang, Yifan; Cai, Sheng; Jiang, Xia; Cai, Xiujun (Frontiers in Nutrition, 2022)
Backgrounds Vitamin D is considered as a nutrient protecting individuals against an array of diseases based on observational studies. Such a protective effect, however, has not been demonstrated by randomized controlled trials. This study aims to explore a putative causal role of vitamin D in common diseases through a two-sample Mendelian randomization (MR) framework. Methods Circulating vitamin D was predicted by 41 genetic variants discovered in European populations. Common diseases were verified through two ways, using information from Japanese patients of Biobank Japan and using information from European patients of FinnGen project. We additionally validated the results by replacing vitamin D-associated instrumental variables (IVs) of European population with that of an independent Japanese population and of an independent Indian population. Inverse-variance weighted method was used as the primary analytical approach while a series of MR methods including MR-Egger regression, weighted median, maximum likelihood, MR-PRESSO and multivariate MR were adopted to guarantee MR model assumptions and to detect horizontal pleiotropy. Results Genetically predicted vitamin D was significantly associated with an increased risk of Graves' disease (OR = 1.71, 95%CI: 1.25–2.33, P = 0.001) and cataract (OR = 1.14, 95%CI: 1.03–1.28, P = 0.016); while with a decreased risk of esophageal cancer (OR = 0.66, 95%CI: 0.46–0.93, P = 0.019). This significant causal link between vitamin D and cataract was validated replacing IVs identified in the European population with those from Japanese population. No notable associations of vitamin D with other diseases were observed. Conclusions Our findings indicate a potential causal role of vitamin D in common diseases, which needs further validation.